L’IMPACT DE L’EDUCATION DIFFUSE EN MILIEU URBAIN : CAS DE LA VILLE DE BUTEMBO (RDC) - Salumu, Fiston WANDJA; Edeline BAYIKERETA KASAY; BAYSONGYA KATAKA Augustin (IJRDO - Journal of Business Management, 2020)
The physical environment of cities is often a danger for education. Most parent move with their families to the city because they imagine they will find a better life there than in the countryside. Send the children to schools in cities where all kinds of temptations await them to attract and pervert them and you will find that character building becomes more difficult for both parents and children at the same time. It is in the cities that the pursuit of pleasure and amusement is concentrated. Many parents who choose to live in the city, hoping to give their children the greatest benefits, repent alas too late and regret their terrible mistake. Today’s cities will quickly become like Sodom and Gomorrah. The many holidays encourage laziness. Exciting sports, but also theater, racing, gambling houses, drinks and entertainment stimulate at the highest level the various passions. Young people, the future of tomorrow, are deviated and trained by the popular current. All over the world, cities are homes in vice and the city of evil; we expect only its rumor following the diffusion of incentives to sensuality and dissipation.